Parking motoring system with security system features - Mohammad Faizal, Mohamad Ehsan (2008)
To easily find an unoccupied parking space in larger car park is a problem for many drivers. During the last four-decade, there are many parking models are develop. But, the models still cannot solve the parking problem. Another problem in parking systems is about security systems. The problem is about how to make sure that the car is safe and this kind of problem involves the security systems. Thus, we have to design a system that can help driver to find parking space easily and at the same time the car that has been park is safe. This project is especially design for private parking space and this system is not suitable for open parking space. The parking space will be monitor by magnetic sensors and the security systems is applied when the user enter the password. So, the user must have a password before they can enter the parking space. Some examples of application for this system are at exclusive club, country club and any private places.